2018
DOI: 10.1186/s12864-018-4996-z
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a high-density genetic map and fine QTL mapping for growth and nutritional traits of Crassostrea gigas

Abstract: BackgroundBoth growth and nutritional traits are important economic traits of Crassostrea gigas (C. gigas) in industry. But few work has been done to study the genetic architecture of nutritional traits of the oyster. In this study, we constructed a high-density genetic map of C. gigas to help assemble the genome sequence onto chromosomes, meanwhile explore the genetic basis for nutritional traits via quantitative trait loci (QTL) mapping.ResultsThe constructed genetic map contained 5024 evenly distributed mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 68 publications
2
20
0
Order By: Relevance
“…Candidate gene association studies showed that six SNPs in the coding region of CgGS were significantly associated with glycogen content (Liu et al, 2017) as well as two SNPs in Cg_GD1 (glycogen debranching enzyme) and one SNP in Cg-GP (glycogen phosphorylase) (She et al, 2015). A high-density genetic map found a QTL explaining 8.6% of glycogen phenotypic variation, and a new gene annotated as a zinc finger protein may participate in glycogen metabolism (Li C. et al, 2018). Many phenotypic variations remain to be explained.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Candidate gene association studies showed that six SNPs in the coding region of CgGS were significantly associated with glycogen content (Liu et al, 2017) as well as two SNPs in Cg_GD1 (glycogen debranching enzyme) and one SNP in Cg-GP (glycogen phosphorylase) (She et al, 2015). A high-density genetic map found a QTL explaining 8.6% of glycogen phenotypic variation, and a new gene annotated as a zinc finger protein may participate in glycogen metabolism (Li C. et al, 2018). Many phenotypic variations remain to be explained.…”
Section: Discussionmentioning
confidence: 99%
“…Glycogen content is a carcass trait that cannot be measured without killing the animal. Indirect selective breeding for glycogen content by morphological traits seems impossible because of the weak correlation between these characteristics, as shown in several studies (Li et al, 2017; Li C. et al, 2018). Thus, molecular breeding is indispensable for the genetic improvement of glycogen content, which requires elucidation of the underlying genetic basis and the identification of genetic variations.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic linkage maps of the Pacific oyster have been constructed based on a variety of molecular markers, including amplified fragment length polymorphism (AFLP) markers or combinations of AFLP with microsatellite markers (Li and Guo, 2004; Guo et al, 2012), microsatellites markers (Li et al, 2003; Hubert and Hedgecock, 2004; Hubert et al, 2009; Plough and Hedgecock, 2011), SNPs (Sauvage et al, 2007; Wang et al, 2015; Qi et al, 2017), and a combination of microsatellite markers with SNPs (Sauvage et al, 2010; Zhong et al, 2014; Hedgecock et al, 2015). Based on these linkage maps, quantitative trait locus (QTL) mapping studies have been performed to examine the genetic basis of growth-related traits in the Pacific oyster (Prudence et al, 2006; Hedgecock et al, 2007a; Guo et al, 2012; Wang et al, 2016; Li et al, 2018). In most of these studies, numerous QTLs associated with growth traits were reported, indicating that growth in oysters is a highly polygenic trait (Qin et al, 2012; Gutierrez et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Regions that failed to be restored to the original assembly or contained an average Hi-C data coverage of less than 0.5% were considered assembly errors, and were broken into smaller scaffolds. Consistency in assembly of Hi-C data based pseudo-chromosomes was assessed by comparisons with a genetic map for the Crassostrea gigas [89] by using software of ALLMAPS [90].…”
Section: Methodsmentioning
confidence: 99%